2020
DOI: 10.1186/s43058-020-00050-4
|View full text |Cite
|
Sign up to set email alerts
|

Predicting implementation: comparing validated measures of intention and assessing the role of motivation when designing behavioral interventions

Abstract: Background Behavioral intention (which captures one’s level of motivation to perform a behavior) is considered a causal and proximal mechanism influencing the use of evidence-based practice (EBP). Implementation studies have measured intention differently, and it is unclear which is most predictive. Some use items referring to “evidence-based practice” in general, whereas others refer to a specific EBP. There are also unresolved debates about whether item stems should be worded “I intend to,” “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 53 publications
(150 reference statements)
1
53
0
Order By: Relevance
“…Within every scientific discipline, scientists strive to develop both uniform definitions and measurement methods for important constructs. Shared terminology and standardized methods enable scientists to collectively advance relevant theory by testing relationships among variables of interest [ 1 ]. Implementation science has been described as “somewhat elusive and overwhelming for researchers” because it has not yet developed distinct construct definitions and associated psychometrically sound instrumentation [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Within every scientific discipline, scientists strive to develop both uniform definitions and measurement methods for important constructs. Shared terminology and standardized methods enable scientists to collectively advance relevant theory by testing relationships among variables of interest [ 1 ]. Implementation science has been described as “somewhat elusive and overwhelming for researchers” because it has not yet developed distinct construct definitions and associated psychometrically sound instrumentation [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, we did not assess vaccination behavioral outcomes, and social desirability may be present with self-reported data. Nonetheless, measures of acceptance are shown to more accurately predict health behavior than alternative variables [ 42 ]. Future research may help determine whether COVID-19 vaccine acceptance would lead to increased vaccination coverage in the real world.…”
Section: Discussionmentioning
confidence: 99%
“…The Theory of Planned Behavior [ 15 ] has shown that two psychological constructs help explain behavior change including smoking cessation: attitudes and self-efficacy [ 16 , 17 , 26 ]. These two constructs include the beliefs that underlie attitudes and self-efficacy towards performing a behavior.…”
Section: Methodsmentioning
confidence: 99%